Collective twitching motility in Pseudomonas aeruginosa and its evolutionary consequences - Meacock, OJ (2019)
From schools of ﬁsh to ﬂocks of birds and herds of wildebeest, the movements of many organisms are characterised by emergent phenomena known as collective movements. These complex group-level behaviours result from simple interactions between individuals. To the naked eye, bacterial colonies appear to be static structures. It might be hard to believe then that collective movements could have any relevance for microbial life. Yet at the microscopic level, many of the same collective phenomena also emerge within microbial systems. In this thesis, I study the collective movements of the opportunistic pathogen Pseudomonas aeruginosa in growing colonies. P. aeruginosa crawls over surfaces by employing twitching motility, utilizing hair-like ﬁlaments known as Type-IV Pili to pull itself forwards. Through a combination of novel experimental and theoretical approaches, as well as a novel cell-tracking package called FAST, I demonstrate that cells at the edge of P. aeruginosa colonies form an active nematic. This class of active matter is characterised by higher-order structures known as topological defects, points where cells with diﬀering orientations meet one another. Two types of defect exist in active nematics: comets and trefoils.